PENERAPAN MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS V SD NEGERI 004 BAGAN TIMUR KABUPATEN ROKAN HILIR - Irawan, Deni; Marhadi, Hendri; Noviana, Eddy (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study is based on the low learning outcomes of IPS students of class V SD Negeri 004 East Bagan Rokan Hilir Regency Year 2016/2017. Initial data received by the researcher, from 20 students who reach the value of KKM only 4 students (20%). This research is a classroom action research conducted collaboratively and participatively in collaboration with class IPS teacher in SD Negeri 004 East Bagan Rokan Hilir Regency. The instrument of this study consists of learning devices used in this study based on Education Unit Level Curriculum (KTSP). Learning tools consist of syllabus, lesson plans, student worksheets and observation sheets. The results obtained by teacher activity on the first cycle of meeting I is 58.33 with enough category, the second meeting of the cycle to I is 70.83 with good category. At siklu II meeting 1 is 79,17 with good category and second meeting second cycle is 91,67 with very good category. Then the percentage of first cycle activity of the first student is 54,17 with enough category, at the second meeting of cycle I that is 70,833 with good category. In the second cycle of meeting I is 83.33 with good category, and meeting II is 87,5 with very good category. As for the result of student learning which complete before held action only 4 student (20%) with average value 54,25. In the daily test I cycle I the number of completed students increased to 8 students or (40%) with an average value of 65.75. Furthermore, in II repetition cycle II increased again with the total number of students who complete as many as 18 students or (90%) with an average value of 83.75. The increase that occurred on student learning outcomes between the basic score of one cycle with an average of 21.19 and between the basic score of the second cycle with an average of 54.37Artinya the classical value obtained by students have been above the established KKM.Keywords: Contextual teaching and learning model (CTL), Learning Outcomes IPS